Policies and progress in science, technology and innovation in defense (2014)
Some countries have achieved economic growth and development relying on the generation of science, technology and innovation, is why the government has included in national development plans the subject of science and technology. Although they have been strengthening programs aimed at the development of projects from universities, these have been truncated by the lack of resources, so much so that Colombia spends less than 0.40% of GDP in CTI, while countries developed invest up to 2%. The defense industry for its part has made technology transfer and is beginning to generate advances in science, technology and innovation for the country, aimed at generating resources.